Adsorção de corante têxtil vermelho reativo 5g utilizando bagaço de cana-de-açúcar como biossorvente - Dall Orsoletta, Gabriel (2013)
Large quantities of textile effluents have been generated in the dyeing of fibers with large load of inorganic salts, organic compounds difficult degradation and intense color, raising many concerns mainly due to its large capacity polluting. The processes used in the treatment of these effluents have difficulty mainly in the removal of color, which does not meet current legislation, in order that the dye molecule can perform chemical bonds that make increase their toxicity. Seeking a better color removal of textile dyes, new alternatives have being studied, to processes cheaper and better efficiency. The biosorption process is a good one for removal of dyes consists in the removal by adsorption (phase shift) of these compounds pollutants through the use of biological material. This work proposes the use of bagasse cane sugar as biosorbent for solution of textile dye reactive red 5G.The bagasse cane sugar it’s better to use was effective in a biomass biosorption of reactive red dye 5G and low cost, as does not require prior treatment and is reused for sugar and alcohol industries.